Radiological evaluation of anatomical changes in implant and adjacent segments after rigid fusion - Ali Malcok, Umit; Aylanc, Nilufer (Annals of Medical Research, 2021)
Aim: We aimed to determine the anatomical remodeling seen after lumbar spine stabilization in detail. Using magnetic resonance images, it is also aimed to reveal this remodeling is not only limited to the adjacent segment and also happens in the upper instrumented vertebra region. At the end of this study, it is suggested to develop new radiological parameters to predict the changes in the adjacent segment and upper instrumented vertebra regions.Materials and Methods: Twenty cases operated for degenerative lumbar stenosis were included in our study. Quantitative data were obtained by radiological measurements by a radiologist and neurosurgeon. On magnetic resonance images, the anatomical structures changed by remodeling were compared before and after the operation during (6-26 months) postoperative period. Unlike previous studies, anterior, middle and posterior disc heights; Cobb angle in the adjacent segment, spinal canal area, bilateral neural foramen, facet joint areas and flavum thicknesses were evaluated.Results: From the sixth month after lumbar fusion, it was observed that angles and anatomical structures were changed in adjacent segment. Also, it was observed that the areas with neural structures expanded in the upper instrumented vertebra region. The degeneration in adjacent segment and relaxation in the upper instrumented vertebra region were found to be statistically significant. A statistically strong positive correlation was found between the number of vertebrae included in the lumbar fusion and the mean height of the adjacent segment disc (r: 0.526, p: 0.017).Conclusion: After comparing the measurements in adjacent segment and upper instrumented vertebra regions before and after the operation, it was concluded that the remodeling was statistically significant. We suggest that the parameters in our study can be used as a scoring method for early detection of adjacent segment degeneration and/or disease. Thus, it will be possible to create follow-up indicators findings after fusion.
Keywords: Adjacent segment; lumbar vertebrae; spinal fusion; upper instrumented vertebra